2020
DOI: 10.3390/dj8030088
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Assisted Depigmentation—An Introspection of the Science, Techniques, and Perceptions

Abstract: Background: Gingival hyperpigmentation is a major concern for a significant number of patients, as a relevant aesthetic or cosmetic need. Oral melanin pigmentation is considered to be multifactorial and could be related to physiological or even pathological reasons and can be the consequence of a variety of local or systemic factors. This pigmentation varies individually across races or age groups and is without any gender predilection. Evidence gleaned from literature is presented from case–control studies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Another described option for melanotic pigmentation management is the use of diode lasers in non-contact mode. The "non-contact" technique with diode lasers without fiber activation is not described in the majority of randomized clinical trials and lacks standardization and evidence with prolonged follow-ups [3].…”
Section: Discussionmentioning
confidence: 99%
“…Another described option for melanotic pigmentation management is the use of diode lasers in non-contact mode. The "non-contact" technique with diode lasers without fiber activation is not described in the majority of randomized clinical trials and lacks standardization and evidence with prolonged follow-ups [3].…”
Section: Discussionmentioning
confidence: 99%
“…According to some researchers, this was the result of thermal damage to tissues by the diode laser 28 . Nevertheless, reduced postoperative pain is the remarkable benefit of the diode laser to the scalpel in early phase wound healing 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Lasers are used in most areas of clinical dentistry and their use is steadily increasing. Their application includes caries detection, caries removal, dental cavity preparation, dentine hypersensitivity management, tooth bleaching, photodynamic therapy, excisional biopsy, aphthous ulcers management, frenectomy, vestibuloplasty, removal of irritation fibroma, removal of hyperplastic tissues, haemangioma, exposure of impacted teeth, gingivectomy and gingivoplasty, apicoectomy, an adjunct to endodontic treatment [ 19 ], gingival melanin hyperpigmentation removal [ 20 , 21 , 22 ], non-surgical periodontal treatment of untreated periodontitis [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] and treatment of peri-implant diseases [ 31 , 32 , 33 ]. In terms of endodontic treatment, lasers are used for post-chemomechanical preparation to reduce the remaining bacterial load either by direct irradiation of the canal walls or by laser assisted irrigation via erbium laser group.…”
Section: The Use Of Lasers In Clinical Dentistrymentioning
confidence: 99%
“…In terms of endodontic treatment, lasers are used for post-chemomechanical preparation to reduce the remaining bacterial load either by direct irradiation of the canal walls or by laser assisted irrigation via erbium laser group. In terms of gingival melanin hyperpigmentation removal, a recent systematic review identified the use of two laser wavelength groups-near infrared diode and erbium group of mid-infrared lasers and failed to draw conclusions on the optimal laser group [ 22 ].…”
Section: The Use Of Lasers In Clinical Dentistrymentioning
confidence: 99%